2021
DOI: 10.1038/s41586-021-03201-2
|View full text |Cite
|
Sign up to set email alerts
|

In situ mapping identifies distinct vascular niches for myelopoiesis

Abstract: Summary In contrast to virtually all other tissues, the anatomy of differentiation in the bone marrow (BM) remains unknown. This is due to a lack of strategies to examine blood cell production in situ, which are required to understand differentiation, lineage commitment decisions, and define how spatial organizing cues inform tissue function. Here we developed approaches to image myelopoiesis and generated atlases of granulocyte and monocyte/dendritic cell differentiation. Granulopoiesis and dendrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(86 citation statements)
references
References 43 publications
1
84
1
Order By: Relevance
“…The CSF1 sinusoids which support myelopoiesis described by Zhang et al (2021) are a subset of type L vessels in the diaphysis. The higher number of CFU-GM colonies seen in the diaphysis might be due to the higher number of sinusoids in the diaphysis than in the epi- and metaphysis ( Zhang et al, 2021 ). The CSF1 sinusoids might affect the formation of the EBIs, as well as their migration toward the sinusoids as the erythroid differentiation progresses from proerythroblast to orthochromatic erythroblasts on the EBIs ( Yokoyama et al, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…The CSF1 sinusoids which support myelopoiesis described by Zhang et al (2021) are a subset of type L vessels in the diaphysis. The higher number of CFU-GM colonies seen in the diaphysis might be due to the higher number of sinusoids in the diaphysis than in the epi- and metaphysis ( Zhang et al, 2021 ). The CSF1 sinusoids might affect the formation of the EBIs, as well as their migration toward the sinusoids as the erythroid differentiation progresses from proerythroblast to orthochromatic erythroblasts on the EBIs ( Yokoyama et al, 2003 ).…”
Section: Discussionmentioning
confidence: 98%
“…Diaphysis has type L vessels which express lower levels of CD31 and endomucin described as CD31 lo EMCN lo (Kusumbe et al, 2014;Ramasamy et al, 2014Ramasamy et al, , 2016. The CSF1 sinusoids which support myelopoiesis described by Zhang et al (2021) are a subset of type L vessels in the diaphysis. The higher number of CFU-GM colonies seen in the diaphysis might be due to the higher number of sinusoids in the diaphysis than in the epi-and metaphysis (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elegant work by Zhang et al revealed that following acute systemic infection, monocyte-dendritic cell progenitors localize to a subset of blood vessels expressing colony-stimulating factor 1 (Csf1), known to be a key regulator of myelopoiesis. Indeed, EC-specific deletion of Csf1, results in a loss of non-classical monocytes and dendritic cells during steady-state and following infection (Zhang et al, 2021). It remains to be elucidated if specialized ECs also support progenitors of lymphoid and erythroid lineages.…”
Section: Velocitymentioning
confidence: 99%